Application of Resistivity Method Wenner-Schlumberger Array to Evaluate Brantas River Embankment as Avoid Landslide - Firdha Kusuma Ayu Anggraeni; Eko Minarto; Arie Realita (Institut Teknologi Sepuluh Nopember, 2017)
The maintenance of embankment is important to avoid some damages like landslide. Brantas river passes 6 cities, include Mojokerto. Landslide of Brantas embankment was occured at Lengkong and Mlirip, Mojokerto. The location of landslide is near from crowded highway. Therefore evaluation using resistivity method is needed to identification vulnerability of landslide. There are 4 line of data acquisition. First, suspected there are seepage at point 25-35 m and fracture at point 65-75 m from dam. Then, second line, there is a suspect of fracture at point 65-90 m and seepage at point 110-125 m. Third line, at point 20-35 m and 110-140 m are suspected as fracture and at point 55-75 m is suspected as seepage. The last line is indicated that the embankment was good.